1979
DOI: 10.1111/j.1570-7458.1979.tb02841.x
|View full text |Cite
|
Sign up to set email alerts
|

AN “INTERVAL TIMER” FOR THE PRODUCTION OF OVIPARAE IN APHIS RUBICOLA (HOMOPTERA: APHIDIDAE)

Abstract: Post‐fundatrix lineages of Aphis rubicola Oestlund exposed to continual short‐day photoregimes of 8 or 10 h resisted sexual‐promoting influences for varying lengths of time. Lineages originating from fundatrices and continually exposed to short days lasted 18.5–31.5 days before consisting of 50% ovipara producers. When 13–67 16‐h days preceded continual short‐day exposure, lineages lasted 11.5–19 days before consisting of 50% ovipara producers. A short‐lived interval timer for the production of oviparae was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
4
9
0
Order By: Relevance
“…A seasonal timer that expires by autumn would be adaptive for responding appropriately to shortened days. The present findings were similar to those of previous studies in M. viciae and A. rubicola: Mothers that had been reared successively under long days and transferred to short days produced many oviparous females (Brodel and Schaefers, 1979;Lees, 1960). These results altogether showed that the sexual polyphenism in aphids is regulated by two mechanisms, and one of them depends on photoperiod whereas the other does not.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A seasonal timer that expires by autumn would be adaptive for responding appropriately to shortened days. The present findings were similar to those of previous studies in M. viciae and A. rubicola: Mothers that had been reared successively under long days and transferred to short days produced many oviparous females (Brodel and Schaefers, 1979;Lees, 1960). These results altogether showed that the sexual polyphenism in aphids is regulated by two mechanisms, and one of them depends on photoperiod whereas the other does not.…”
Section: Discussionsupporting
confidence: 92%
“…The present results show that in A. pisum, the seasonal timer measured the number of days from hatching, not the number of generations, in accord with the reported findings in M. viciae and A. rubicola (Brodel and Schaefers, 1979;Lees, 1960).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The similar results were obtained in experiments with Aphis chloris Koch. Aphis rubicola Oestlund, Drepanosiphum platanoides (Schrank), Eucallipterus tiliae L., Myzus persicae (Sulzer), and Phorodon humuli (Schrank) although in these aphids, the ability to produce sexuales gradually increased over several generations (Brodel and Schaefers, 1979;Campbell and Tregidga, 2006;Dixon, 1971Dixon, , 1972Margaritopoulos et al, 2002;Wilson, 1938). It is interesting that we have found both gradual (in T. principium) and relatively rapid (in T. telengai) waning of the maternal restraining effect.…”
Section: Discussionmentioning
confidence: 86%
“…Of course, metabolic and signal mechanisms are not mutually exclusive, but long-term effects are most probably based on transfer of signals rather than nutrients. In the regulation of insect diapause, these effects are often manifested as 'interval timers' which measure time intervals independently of the number of elapsed generations, although 'generation counters' reducing the effect in accordance with the number of generations passed can be also conceived (Brodel and Schaefers, 1979;Campbell and Tregidga, 2006;Denlinger, 1998Denlinger, , 2002Dixon, 1971Dixon, , 1972Lees, 1960Lees, , 1966Lushai et al, 1996;Margaritopoulos et al, 2002;Ogawa and Miura, 2014;Saunders et al, 2002). At present, biochemical and molecular mechanisms of diapause induction are intensively investigated (Denlinger, 2002;Denlinger et al, 2012) but 'classic physiological experiment' still remains an important tool for future studies (Goto and Numata, 2014).…”
Section: Introductionmentioning
confidence: 98%